The nana project [videorecording (DVD)] - Moellenberg, Carl; Del Negro, Anthony; Ulloa, Eric; Ruehl, Mercedes; Gould, Nolan; Peltz, Will, 1986-; Fairchild, Morgan (Gravitas Ventures, 2024)
Set primarily at Timeless Acres Retirement Home, the film follows a documentary crew who develop an interest in one of its star resident's feisty chess master Helen "Nana" Lewis. With the help of her friends Jennifer, Francesca, Jack, Esther, Kitty, Gladys, and Lisa, Nana begins training for the State Chess Championship. She plans on dominating the competition, but her real plan involves reuniting her estranged grandsons, Andrew, a dedicated veterinary student and Cody, a flashy male model and influencer. We follow Nana's journey in a hilarious and heartwarming family comedy about getting older and coming back together again.